Improvement of Very Shallow Soil by Hybridizing with Tank Silt: A Case Study from Osmanabad District, Maharashtra - P.H. Vaidya; N.M. Patil; S.P. Zade; C.V. Ambadkar; A.S. Dhawan (Journal of the Indian Society of Soil Science, 2024)
Very shallow soil hybridized with tank silt recover the soil quality and productivity. Recycling of tank silt provides a win-win situation for improvement in soil health and renovation of the tank. The improvement of very shallow soil by hybridizing with tank silt, study was undertaken with quality of tank silt and its hybridizing effect on soil characteristics and yield of crops. The tank silts were found dark brown (10YR3/ 2) to black (10YR2.5/2) in colour, clay content varied from 48.7 to 76.3%, bulk density varied from 1.2 to 1.4 Mg m-3, hydraulic conductivity in between 0.75 to 3.4 cm h-1, high plant available water capacity (PWAC) > 250 mm, slightly to moderately alkaline (pH 7.3-8.1), electrical conductivity (EC) <1 dS m-1, low to high organic carbon (OC) (0.2-1.1%) and calcareous (3.8-22.5%) in nature. Cation exchange capacity (CEC) varied from 45.1 to 71.2 cmol(p+)kg-1, available nitrogen (N) low to medium (220-357 kg ha-1), available phosphorus (P) medium to very high (11.5-28.1 kg ha-1) and available potassium (K) medium to very high (198-809 kg ha-1). The DTPA extractable micronutrients viz., iron (Fe), zinc (Zn), copper (Cu), and manganese (Mn) were found in the range of 12.5-63.2, 0.6-2.4, 3.0-17.0 and 7.2-21.4 mg kg-1, respectively. The DTPA extractable heavy metals viz., lead (Pb), nickel (Ni), and cadmium (Cd) in tank silt varied from 1.0 to 2.6, 0.4 to 2.0 and 0.01 to 0.08 mg kg-1, respectively which were below the safe limit. The hybridization effect of tank silt in very shallow soils showed two- to three-folds increase in clay content, PAWC, and CEC; whereas three-fold increase in the yield of commonly grown crops. The correlation between the rate of hybridization of tank silt in very shallow soil and yield of crops such as soybean, cotton, pigeon pea, and sorghum were found significantly positively correlated (r = 0.49, 0.69, 0.92 and 0.49, respectively) and also significantly positively correlated with clay content, moisture content and CEC (r = 0.51, 0.58 and 0.69, respectively) and negatively correlated with hydraulic conductivity (r = - 0.93). Initial year of tank silt hybridization benefit: cost ratio (B: C) was <1 (0.33-0.47), thereafter it was increased by 2-3 folds. The average B:C ratio after eight years under single crop was 1.65 and double crop was 1.64, whereas <1 under without tank silt hybridized soils. This indicated that tank silt hybridization improves soil health of very shallow soil and the yield of crops and could be an economically viable option for improvement in very shallow soil, thereby unproductive land comes under productive for a longer period on a sustainable basis.